Ecological and Legal Problems of Electrification of Motor Vehicles - I. V. Bryhadyr (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on studying the state policy, legislation and practice of its application in Ukraine regarding the use of electrified motor vehicles – battery vehicles that run on chemical sources of electric current. The purpose of the work is to determine the legal mechanisms to prevent the negative impact on the environment from the electrification of motor vehicles.